Epidemiology of injuries in National Collegiate Athletic Association men's cross-country: 2014-2015 through 2018-2019 - Chandran, A.; Morris, S. N.; Boltz, A. J.; Robison, H. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association has sponsored men's cross-country programs since 1938, and the sport has grown greatly in scope since then. Background: Routine examinations of men's cross-country injuries are important for identifying emerging temporal patterns. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program during 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 4.01 per 1000 athlete-exposures (AEs). Most reported injuries were inflammatory conditions (30.2%), strains (18.7%), and sprains (11.5%); rates of inflammatory conditions were highest in preseason. The most commonly reported injuries were lateral ligament complex tears (ankle sprains; 8.2%). Summary: Findings of this study were not entirely consistent with existing evidence; continued monitoring of competition injury rates and rates of commonly reported injuries is needed beyond 2018-2019.